Efficacy assessment of a triple anthrax chimeric antigen as a vaccine candidate in guinea pigs: challenge test with Bacillus anthracis 17 JB strain spores. (4th July 2021) - Abdous, Masoud; Hasannia, Sadegh; Salmanian, Ali Hatef; Arab, Seyed-Shahryar
Abstract: Context: Bacillus anthracis secretes a tripartite toxin comprising protective antigen (PA), edema factor (EF), and lethal factor (LF). The human anthrax vaccine is mainly composed of the anthrax protective antigen (PA). Considerable efforts are being directed towards improving the efficacy of vaccines because the use of commercial anthrax vaccines (human/veterinary) is associated with several limitations. Objective: In this study, a triple chimeric antigen referred to as ELP (gene accession no: MT590758) comprising highly immunogenic domains of PA, LF, and EF was designed, constructed, and assessed for the immunization capacity against anthrax in a guinea pig model. Materials and methods: Immunization was carried out considering antigen titration and immunization protocol. The immunoprotective efficacy of the ELP was evaluated in guinea pigs and compared with the potency of veterinary anthrax vaccine using a challenge test with B. anthracis 17JB strain spores. Results: The results demonstrated that the ELP antigen induced strong humoral responses. The T-cell response of the ELP was found to be similar to PA, and showed that the ELP could protect 100%, 100%, 100%, 80% and 60% of the animals from 50, 70, 90, 100 and 120 times the minimum lethal dose (MLD, equal 5 × 10 5 spore/ml), respectively, which killed control animals within 48 h. Discussion and conclusions: It is concluded that the ELP antigen has the necessary requirement for proper immunization against anthrax and it can be used to develop an effective recombinant vaccine candidate against anthrax.